2002
DOI: 10.1596/1813-9450-2784
|View full text |Cite
|
Sign up to set email alerts
|

Financial and Legal Constraints to Firm Growth: Does Size Matter?

Abstract: Using a unique firm-level survey data base covering 54 promoting firm growth, particularly the development of countries, Beck, Demirgiu,-Kunt, and Maksimovic the small and medium enterprise sector. But the evidence investigate whether different financial, legal, and also shows that the intuitive descriptors of an "efficient" corruption issues that firms report as constraints actually legal system are not correlated with the components of affect their growth rates. The results show that the extent the general l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
766
4
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 590 publications
(814 citation statements)
references
References 36 publications
36
766
4
8
Order By: Relevance
“…Financial institutions are less likely to lend money to entrepreneurs because of the high risk associated with the endeavor and the lack of information (Berger and Udell 1998). Prior research suggests that the limited availability of financial resources has a significant negative impact on entrepreneurs regardless of the types of the entrepreneurial activity (Beck et al 2005). Based on these observations, we expect that greater availability of financial resources will induce all types of entrepreneurial activity:…”
Section: Availability Of Financementioning
confidence: 98%
“…Financial institutions are less likely to lend money to entrepreneurs because of the high risk associated with the endeavor and the lack of information (Berger and Udell 1998). Prior research suggests that the limited availability of financial resources has a significant negative impact on entrepreneurs regardless of the types of the entrepreneurial activity (Beck et al 2005). Based on these observations, we expect that greater availability of financial resources will induce all types of entrepreneurial activity:…”
Section: Availability Of Financementioning
confidence: 98%
“…While the business environment indicators refer to firms of all sizes, previous research has shown that financial and institutional underdevelopment constrains the growth and operation of small and medium size firms significantly more than that of large firms (Beck et al, 2005b). In this section, we first discuss different business environment indicators and how they might be related to the size of the SME sector and the informal economy and then employ regression based ANOVA to assess the extent to which cross-country variation in business environment can explain cross-country variation in the size of the SME sector and the informal economy.…”
Section: Smes the Informal Economy And The Business Environmentmentioning
confidence: 99%
“…Using a firm-level survey of small, medium-sized and large enterprises in 80 developing, developed and transition economies, Schiffer and Weder (2001) show that small firms face significantly higher growth obstacles in several areas, such as financing, taxation and regulation, exchange rate management, corruption, street crime, organized crime, and anti-competitive practices by other enterprises or the government. Using the same dataset, Beck, et al (2005) show that the relationship between financial, legal and corruption obstacles and firm growth is stronger for small firms and in countries with lower levels of financial and institutional development. These papers do not, however, show that countries with larger SME sectors enjoy greater economic success.…”
Section: Measures Of Smes and Business Environmentmentioning
confidence: 99%